Effects of hypertensive disorders of pregnancy on the complications in very low birth weight neonates - Baoquan Zhang; Xiujuan Chen; Changyi Yang; Huiying Shi; Wenlong Xiu (Hypertension in Pregnancy)
Objective This study was designed to investigate the effects of hypertensive disorders of pregnancy (HDP) on the complications in very low birth weight (VLBW) neonates.Methods We retrospectively included VLBW neonates (<37 weeks) who were delivered by HDP pregnant women with a body weight of < 1,500 g (HDP group) hospitalized in our hospital between January 2016 and July 2021. Gestational age matched VLBW neonates delivered by pregnant women with a normal blood pressure, with a proportion of 1:1 to the HDP group in number, served as normal control.Results Then we compared the peripartum data and major complications between HDP group and control. The body weight, prelabor rupture of membrane (PROM), maternal age, cesarean section rate, fetal distress, small for gestational age (SGA), mechanical ventilation, RDS, necrotizing enterocolitis (NEC) (≥2 stage), Apgar score at 1 min, and mortality in HDP group showed statistical differences compared with those of the control (all p < 0.05). To compare the major complications among HDP subgroups, we classified the VLBW neonates of the HDP group into three subgroups including gestational hypertension group (n = 72), pre-eclampsia (PE) group (n = 222), and eclampsia group (n = 14), which showed significant differences in the fetal distress, Apgar score at 1 min, SGA, ventilation, RDS and NEC (≥2 stage) among these subgroups (all p < 0.05). Multivariate regression analysis showed that eclampsia and PE were the independent risk factors for SGA and NEC, respectively.Conclusion HDP was associated with increased incidence of neonatal asphyxia, fatal distress, SGA, mechanical ventilation, RDS, NEC and mortality. Besides, eclampsia and PE were independent risk factors for SGA and NEC.